2012
DOI: 10.3390/mi3020345
|View full text |Cite
|
Sign up to set email alerts
|

Strong Electro-Absorption in GeSi Epitaxy on Silicon-on-Insulator (SOI)

Abstract: Abstract:We have investigated the selective epitaxial growth of GeSi bulk material on silicon-on-insulator substrates by reduced pressure chemical vapor deposition. We employed AFM, SIMS, and Hall measurements, to characterize the GeSi heteroepitaxy quality. Optimal growth conditions have been identified to achieve low defect density, low RMS roughness with high selectivity and precise control of silicon content. Fabricated vertical p-i-n diodes exhibit very low dark current density of 5 mA/cm 2 at −1 V bias. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Using the Franz-Keldysh (FK) effect in Ge or GeSi alloy, very short (∼50 μm) EA modulators have been demonstrated [63]- [67], with efficiency of ∼2 dB/V and speeds beyond 40 Gb/s. These devices typically have high waveguide loss (>0.1 dB/μm) caused by indirect-bandgap absorption and epitaxial material defects.…”
Section: Modulator Candidates In Simentioning
confidence: 99%
“…Using the Franz-Keldysh (FK) effect in Ge or GeSi alloy, very short (∼50 μm) EA modulators have been demonstrated [63]- [67], with efficiency of ∼2 dB/V and speeds beyond 40 Gb/s. These devices typically have high waveguide loss (>0.1 dB/μm) caused by indirect-bandgap absorption and epitaxial material defects.…”
Section: Modulator Candidates In Simentioning
confidence: 99%
“…65 Technically, this data is for a Si 0.006 Ge 0.994 alloy. [184]) and QCSE (data after [82]) electroabsorption. The FKE data is taken in a SiGe diode structure with a ~2μm thick depletion region with ~ 0.6% fractional Si content (so technically a Si 0.006 Ge 0.994 alloy) so as to shift the absorption edge slightly to shorter wavelengths from that of pure Ge.…”
Section: Electroabsorption Mechanisms and Approachesmentioning
confidence: 99%
“…12 These components were designed with substitutional and vacancy defects on the 111 surface of 3C-SiC and 3C-GeSi, while both the materials [13][14][15][16] and the defects [17][18][19] can be produced experimentally. Although phononic waveguides and resonators have been studied in much larger scales, [20][21][22][23] this study 12 showed that they can be scaled down to the nanometer or even in the atomic dimensions.…”
Section: Introductionmentioning
confidence: 99%